Dynamic Modelling Of Bioelectrochemical Activity For Anode Microbial Fuel Cells By Geobacter Sulfurreducens_ - Shoparwe, Noor Fazliani (2016)
Microbial fuel cells are an emerging technology which shows great potential for the generation of electricity from organic substrate via microbial and electrochemical reactions. This research project was carried out to improve bioelectrochemical activity of anode microbial fuel cells for electric current generation by using Geobacter sulfurreducens as a biocatalyst. In performing these studies, the dynamic modelling focusing for an anode side in a batch system was developed. The mechanism of direct electron transfer from the extracellular cells to an electrode was considered. The improvement of the model was made by taking into account the kinetic of biochemical and electrode reaction, and combined with the voltage losses of the system. The improvement was also made on biochemical reaction by considering the deactivation rate of enzyme reaction. The mathematical model allows studying the electric current profile, biomass production, substrate consumption and voltage losses as function of time. The experimental works at different operating conditions were performed to determine the important parameters and validated the mathematical model. Electrochemical methods were applied to perform the electrochemical activity of the system. Polarization curve was used to examine the individual voltage losses such as activation loss, Ohmic loss and concentration loss. Electrochemical impedance spectroscopy (EIS) was applied to determine the internal resistance and polarization resistance parameters. In addition, cyclic voltammetry (CV) method was used to perform the electrode kinetic studies of the system at different scanning rate and applied voltage. The optimum result obtained from the experimental studies using single chamber design, graphite felt as an electrode and 20 mM of initial acetate concentration which gave the optimum electric current production of 2.32 mA, the internal resistance of 85.24 Ω, the specific growth rate of 0.068 h-1, the maximum yield of cell biomass for Geobacter sulfurreducens of 0.0196 gcell.gacetate-1, and the heterogeneous electron transfer rate for anode of 0.0018 cm.s-1 was used to validate the model. The dynamic model was successfully validated with the experimental data which gave mean square error less than 10%. The overall work in this research project has successfully addressed and help to overcome several challenges in the development of microbial fuel cell technology. The combination of bioelectrochemical process with mathematical model has not only open a great potential for enhancing the microbial fuel cells performance but help us to fully understanding the overall system of microbial fuel cells.